O gênero Carapa Aubl. nas terras baixas da Amazônia e Guiana Francesa: uma abordagem integrativa para delimitação de espécies incluindo os aspectos evolutivos da poliembrionia. - Amoêdo, Semírian Campos (Botânica, 2024)
Research dedicated to delimiting plant species is fundamental to understanding the evolutionary processes that lead to the formation of “species complexes”, although it is challenging due to the varied reproductive strategies and phenotypic plasticity that plants display, especially in areas of high biodiversity such as the Amazon rainforest. This study aims is to understand the phylogenetic relationships between Carapa species, recognizing the species that occur in populations in the lowlands of the Amazon and the evolutionary relationships between these species and polyembryony. In Chapter 1, we investigated the distribution, morphology, and spectral characteristics of three species of Carapa (C. guianensis, C. surinamensis, and C. vasquezii). Areas of greater suitability for the occurrence of the species were identified through predictive modeling, with the Mahalanobis and Random Forest algorithms, demonstrating high accuracy in predicting the distribution of the species. The morphometric analysis identified important variations such as the size and shape of the petioles and leaflets that distinguish between the species. Discriminant Analysis of Principal Components (DAPC) supports the differentiation of species. Spectral analysis showed promise in helping to distinguish the species. This study highlights the complexity of delimiting species using only morphological characters and underlines the need for integrated approaches to understanding the biodiversity and conservation of Carapa species in the Amazon region. In Chapter 2, we investigated the diversity and genetic structure of Carapa using 35 SSRseq markers developed exclusively for this study, which successfully amplified 167 samples. A total of 558 alleles, 147 distinct multilocus genotypes, and a Nei genetic diversity range between 0.15 and 0.93 were identified. The genetic structure explored using Bayesian cluster analysis, identified a robust solution with four genetic clusters, showing homogeneity in the proportions of ancestry and corresponding, in most cases, to the species groups defined a priori. However, individuals with mixed genotypes showed ancestry in more than one cluster, highlighting the complexity of the taxonomic assignment and requiring further investigation into the hypotheses of interspecific hybridization and the influence of planting activities on species delimitation. The genetic diversity indices and the Analysis of Molecular Variance (AMOVA) showed a high rate of polymorphism and genetic variability both within and between clusters, with 85% of the variation occurring within clusters. This supports the distinction between morphologically determined botanical species and their genetic groupings. In addition, genetic distance analysis and the minimum spanning network highlighted the genetic relationships within clusters and between different geographical localities, challenging traditional taxonomic classifications and pointing to the need for an integrative approach to the conservation of Carapa species. Chapter 3 investigated the genetic basis of polyembryonic seeds of Carapa spp. by measuring polyembryony, assessing genetic variability between seedlings, and differentiating asexual from sexual reproduction. Polyembryony varied between sites, with Manaus showing 77% and Apuí at 17%. High genetic diversity was observed, with many alleles per locus and variation in diversity indices. Among the 203 seedlings analyzed, 103 multilocus genotypes (MLG) and 29 multilocus lineages (MLL) were identified, indicating clonality among the samples. Manaus showed high clonality and low genotypic diversity, while Juriti showed high genetic diversity and no clones. The analysis of genetic variance (AMOVA) revealed significant variation between populations, suggesting a clear genetic distinction. Environmental, genetic, and human management factors influence polyembryony. High polyembryony in Manaus is associated with genetic homogeneity, while genetic diversity is maintained in populations with predominant sexual reproduction. Polyembryony is related to domestication and management factors, impacting the reproduction, evolution, and genetic diversity of Carapa species.
Keywords: Complexo de espécies; Andiroba; SSR-Seq